2003
DOI: 10.1046/j.1365-2036.2003.01783.x
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive guaiac faecal occult blood test is less useful than an immunochemical test for colorectal cancer screening in a Chinese population

Abstract: SUMMARYBackground: Colorectal cancer screening by guaiac faecal occult blood test has been shown to reduce the incidence and mortality of colorectal cancer in Western populations. The optimal faecal occult blood test, whether guaiac or immunochemical, for colorectal cancer screening in the Chinese population remains to be defined. Aim: To compare the performance characteristics of a sensitive guaiac-based faecal occult blood test (Hemoccult SENSA) and an immunochemical faecal occult blood test (FlexSure OBT) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 16 publications
(19 reference statements)
1
44
0
2
Order By: Relevance
“…Several studies have previously shown that the Hemoccult II Sensa test can give unexpectedly high positive rates in certain populations, probably because of failure to follow dietary recommendations. 13,34 FITs are not subject to such an effect in those populations. 13,34 Although this study has been directed toward examining relative effectiveness for detection of neoplasia, the FIT technology also has distinct behavioral advantages.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Several studies have previously shown that the Hemoccult II Sensa test can give unexpectedly high positive rates in certain populations, probably because of failure to follow dietary recommendations. 13,34 FITs are not subject to such an effect in those populations. 13,34 Although this study has been directed toward examining relative effectiveness for detection of neoplasia, the FIT technology also has distinct behavioral advantages.…”
Section: Discussionmentioning
confidence: 91%
“…13,34 FITs are not subject to such an effect in those populations. 13,34 Although this study has been directed toward examining relative effectiveness for detection of neoplasia, the FIT technology also has distinct behavioral advantages. Patients are more likely to participate, i.e., complete and return the test sampling kit, when diet and drug restrictions are removed 20 and when a simpler sampling procedure, such as the brush method combined with reduced number of samples, is used.…”
Section: Discussionmentioning
confidence: 91%
“…The lower specificity of our results may be explained by the fact that the Chinese diet often contains components that may cause a false-positive CFOBT. 18 It appears that the third sample had more false-positive finding than the first 2 samples combined. The reason for that is unclear.…”
Section: Discussionmentioning
confidence: 96%
“…In this review, we have focused on studies that compared different FIT with Hemoccult SENSA since at present it has the highest sensitivity of currently marketed gFOBT. 49,[54][55][56][57][58] Based on data from these 6 studies, it appears that there are no clear patterns of superior performance in overall test performance between a high-sensitivity guaiac-based test (Hemoccult SENSA) and a variety of FIT.…”
Section: Fitmentioning
confidence: 99%